CONTROLE DE GESTION ET PERFORMANCE DES ENTITES TERRITORIALES DECENTRALISEES EN REPUBLIQUE DEMOCRATIQUE DU CONGO CAS DE LA VILLE DE KISANGANI : DE 2009 à 2018 - MADIGO MBINZA Bienvenu (IJRDO - Journal of Social Science and Humanities Research, 2020)
Our Article is essentially a state of the literature that aims (1) to present the different aspects of the concept of management control as instrument, of decentralization and the performance of the territorial collectivities decentralized (2) to sketch the different tools of performance used in the decentralized territorial entities and (3) to verify if the endogenous variables permitted that the entity territorial decentralized are effective. This state of the literature allowed us to note that all indicators of performance and all tools of piloting of the performance in force in the classic organizations can also be adapted to the decentralized territorial entities. He/it is evident from the literature that at all times the budget is the tool the more used. Of other modern tools as the benchmarking, the control panel and the balanced scorecard are little more and more in vogue in decentralized territorial entities.